ANALISIS KOMPONEN VISUAL PESAN MASKULINITAS PADA SERIES PEAKY BLINDERS SEASON 6 - Reza Gunawan; Anita Pahlevi (Kinesik, 2023)
The purpose of this study is to identify aspects of the message of masculinity in the series of Peaky Blinders season 6 using the concept 5c’s of cinematography 5c proposed by Joseph V Mascelli. The results of this study, was found out of that the dominant element is the big wheel as this element is present in every episode, while the rarest is be a sturdy oak. Then it was also proven that how the 5C technique in cinematography managed to convey a message. Such as the angle of placement of a high angle camera that describes how a character is being bullied, a low angle that describes the valor of a character; Unsuccessful image continuity without scene by scene so that the image does not feel sloppy; The technique of cutting images or cutting which is also able to give meaning to each transition from the scene and the shot; The distance from the camera that frames the gesture or body language of a character, the audience only sees what the filmmaker wants to show; then the composition technique applied by the filmmaker to add an aesthetic element to each shot image.